Chess international titleholders, 1950-2016 - Di Felice, Gino, 1955- (McFarland & Company, Inc., Publishers, 2017)
"This works aims to gather in one volume the players who received international titles from 1950 through December 2016. This volume lists as many as 18,000 names in alphabetical order. Names are given as they appear in FIDE's List of Players. Federations are given according to FIDE's three-letter abbreviations. The book is completed by a list of sources"--